What is the mind map of the hospital's future changes in a developing country like Iran? A qualitative study - Ali Masoud; Reza Dehnavieh; Vahid Yazdi-Feyzabadi; Atousa Poursheikhali; Somayeh Noori Hekmat; Mohammad kazemi; Mina Ghasemi Moghadam (BMC, 2023)
Abstract Background Hospitals have a vital role in the future of health systems with upcoming structure, resources, and process changes. Identifying the potential aspects of change helps managers proactively approach them, use the opportunities, and avoid threats. This study presents a mind map of future changes in Iranian hospitals to develop a base for further related studies or prepare evidence for interventions and future-related decisions. Methods This study is a qualitative-exploratory one, conducted in two phases. In the first phase, in-depth and semi-structured interviews were conducted to identify future hospital changes over 15 years. The interviews were analyzed using the content analysis method and MAXQDA 2018 software and holding two expert panels to develop the mind map using the 2016 Visio software. Results In the first phase, 33 interviews led to 144 change patterns. In the second phase, a mind map of changes was drawn according to experts' opinions with ten categories: structure and role, knowledge management and research, service delivery, health forces, political and legal, economic, demographic and disease, technological, and values and philosophy, and environmental. Conclusions Many changes affecting hospitals rooted in the past continue to the future, but the point is the increasing intensity and speed of changes. Healthcare systems need a systematic approach to monitoring the environment to be updated, agile and proactive. These monitoring systems are essential in providing evidence for Macro-level decision-makers.